Occupational Stress among Nurses in a Public Medical College Hospital (Delta Medical College Journal, 2018)
Background: Now a days, there is increased demand and progress in the nursing profession. Along with these stress among the nurses has also increased.Objective: Purpose of the study was to assess the extent of perceived occupational stress and its association with work-related and non-work related causes among nurses.Materials and method: This Cross-sectional study was carried out among 197 nurses of Shaheed Suhrawardy Medical College hospital (ShSMCH), Dhaka, Bangladesh, from the period of 1st July 2015 to 30th June 2016. Sampling method was simple random sampling. Data was collected by face to face interview with the help of semi-structured questionnaire and finally all data were analyzed using SPSS software version 21.Results: It was found that 69% nurses were between the age of 21 to 39 years, 94.9% were female, 68% were married, 79.2% were Muslim, 84.3% had diploma, family income of 91.4% were equal to more than 40,000 Tk. and 95.5% used to do clinical work. Only 5.1% found to experience high stress. Statistically significant difference was found between sex, occupational stress and religion, educational status, and type of work (p < 0.05). Few nurses suffered from high stress but high level of stress were more in male, non Muslim, post graduate nurse and those who were engaged in administrative work.Conclusion: Nurse Managers should take appropriate actions to decrease stress helping their nurses to work efficiently and effectively.Delta Med Col J. Jan 2018 6(2): 86-89